Anarcho Movement Against State Capitalism as A Form of Political Antagonism (Case Study of Anarcho Syndicalist Direct Action on Mayday 2019) - Shinta Ressmy Cakra Ningrat; Nanang Suryana (Epistemik Press, 2020)
Anarchism is a new tool of struggle for society, especially anarcho syndicalist is an alternative form of mass struggle which concentrates on the labor group as the pillar of the liberation teacher and is considered a philosophy of the workers. This is at least evidenced by the Mayday 2019 direct action. The anarchism movement itself is a representation of the political antagonism movement. This journal uses two main theories. First, Cheryl Simrell King & Camila Stivers's theory states that political antagonism is part of the representation of a vehicle for counter-state movements. Second, the theory used is the theory put forward by Mikhail Bakunin regarding the concept of freedom. This study uses qualitative research methods with primary and secondary data.